2021
DOI: 10.1097/qad.0000000000003126
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of V114, a 15-valent pneumococcal conjugate vaccine, in adults living with HIV

Abstract: Objectives: To evaluate safety and immunogenicity of V114 [15-valent pneumococcal conjugate vaccine (PCV) containing serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, 22F, 23F, and 33F], followed by 23-valent pneumococcal polysaccharide vaccine (PPSV23) 8 weeks later, in adults living with HIV. Design: In this phase 3 study (V114-018; NCT03480802), pneumococcal vaccine-naive adults with HIV (CD4 + cell count ≥50 cells/μl, plasma HIV RNA <50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Most individuals in both vaccination groups reported at least one adverse event, most commonly injection‐site reactions (63.8% of patients receiving PCV15 and 54.7% receiving PCV13). The percentage of individuals with injection‐site reactions, systemic adverse events, and vaccine‐related adverse events was comparable 50 …”
Section: Clinical Datamentioning
confidence: 92%
See 4 more Smart Citations
“…Most individuals in both vaccination groups reported at least one adverse event, most commonly injection‐site reactions (63.8% of patients receiving PCV15 and 54.7% receiving PCV13). The percentage of individuals with injection‐site reactions, systemic adverse events, and vaccine‐related adverse events was comparable 50 …”
Section: Clinical Datamentioning
confidence: 92%
“…In addition, the immune response elicited by PCV15 was found to be superior to PCV13 for the common serotype 3 and for serotypes 22F and 33F, both of which are unique to PCV15. Clinical trials revealed no significant difference in immune response in patients 65–74 and 75 years and older compared with younger individuals 48–55 . There are currently no published studies on the clinical effectiveness of PCV15.…”
Section: Clinical Datamentioning
confidence: 96%
See 3 more Smart Citations